(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2022)
The purpose of this article is the contrastive study of somatisms created from the eye. This work is divided into three parts. In the first, light is shed on the theoretical framework in which our research is located: cognitivism. Theories of metaphor, metonymy, and the embodiment of cognition and language, embodiment, receive special interest. The second part is occupied by the corpus, with somatisms of Spanish collected from the Dictionary of the Royal Academy. In this section we analyze a corpus of somatisms about the eye and its translation into Italian, and we try to classify them according to the metaphorical and metonymic elements present in them. The study ends with a general conclusion and bibliographical references.